The influence of the initial size of the tetragonal phase zirconium oxide powder in the formation of a thermal protection barrier - Zavaleta Tisnado, Jhonattan Omar (2020)
In this work we study the effects on the porosity and microhardness properties when using different ZrO2 + 8% Y2O3 diameters powders (less than 40 μm, between 40 to 60 μm and greater than 80 μm) to deposit in the upper layer of a TBC system (thermal barrier coating) of double layer formed by NiCrCoAlY and ZrO2 + 8% Y2O3 using the plasma spray process, in order to find the suitable powder and feasible to use as top layer. To this end, instruments such as  TESCAN Vega SB scanning electron microscope with INCA Energy dispersive microanalyzer were used, with which it was possible to detect the porosity in different areas of evaluation of the upper layer and the Vickers durometer to measure the microhardness. Verifying that with particle diameters smaller than 40 μm, the aforementioned properties are adequate for the conformation of the ZrO2 + 8% Y2O3 top layer.